Mechanism and early intervention research on ALI during emergence surgery of Stanford type-A AAD: Study protocol for a prospective, double-blind, clinical trial. Issue 42 (October 2016) - Cheng, Yi; Jin, Mu; Dong, Xiuhua; Sun, Lizhong; Liu, Jing; Wang, Rong; Yang, Yanwei; Lin, Peirong; Hou, Siyu; Ma, Yuehua; Wang, Yuefeng; Pan, Xudong; et al.
Abstract: Background: Stanford type-A acute aortic dissection (AAD) is a severe cardiovascular disease demonstrating the characteristics of acute onset and rapid development, with high morbidity and mortality. The available evidence shows that preoperative acute lung injury (ALI) induced by Stanford type-A AAD is a frequent and important cause for a number of untoward consequences. However, there is no study assessing the incidence of preoperative ALI and its independent determinants before Standford type-A AAD surgery in Chinese adult patients. Methods/design: This is a prospective, double-blind, signal-center clinical trial. We will recruit 130 adult patients undergoing Stanford type-A AAD surgery. The incidence of preoperative ALI will be evaluated. Perioperative clinical baselines and serum variables including coagulation, fibrinolysis, inflammatory, reactive oxygen species, and endothelial cell function will be assayed. The independent factors affecting the occurrence of preoperative ALI will be identified by multiple logistic regression analysis. Trial registration: ClinicalTrials.gov (https://register.clinicaltrials.gov/ ), Registration number NCT01894334.